A high-output-current and low-power-loss thin-film transistor liquid-crystal display (TFT-LCD) driver for portable devices. (1st January 2012) - Mok, K.T.; Lai, Y.M.; Loo, K.H.; Chan, W.C.; Lee, C.F.; Lai, Stephen W.Y.
The application range of traditional thin-film transistor (TFT) liquid-crystal display (LCD) drivers powered by switched-capacitor DC-DC converters (charge pumps) used in portable devices are, to a certain extent, restricted because of their inability to support applications that require high driving current for generating high resolution graphics or powering larger LCD panels. This paper reviews the limitations of charge pumps when used on TFT-LCD drivers fabricated using the chip-on-glass (COG) packaging technology. A high-output-current low-power-loss boost-type DC-DC converter is proposed to replace traditional charge pumps while retaining the existing COG packaging technology in order to reduce production cost. A prototype of the proposed converter is designed with a standard 0.13 µm HV CMOS process. Compared with traditional designs, the proposed converter demonstrates that it is capable of delivering a higher driving current at a much smaller power loss.